Case report: Response to everolimus in a patient with platinum resistant, high grade serous ovarian carcinoma with biallelic TSC2 inactivation - Peterson, Mariko; Kolin, David L.; Konstantinopoulos, Panagiotis A. (Frontiers in Oncology, 2024)
Background: Patients with platinum-resistant recurrent high grade serous ovarian carcinoma have poor outcomes and limited treatment options.We present a case of a 48-year-old woman with platinum-resistant high grade serous ovarian carcinoma harboring the pathogenic TSC2 R611Q variant with concomitant single copy loss of TSC2 (suggesting biallelic TSC2 inactivation) identified in targeted tumor sequencing.The patient was treated with the mTOR inhibitor everolimus, with an excellent response by imaging and a marked decrease in CA125; she remained on everolimus for 19 months until she developed progressive disease.While mTOR inhibition is frequently used in tumors associated with tuberous sclerosis complex (TSC), such as lymphangioleiomyomatosis and malignant perivascular epithelioid cell tumors, this is the first case of a patient with ovarian cancer harboring TSC1/2 mutations who responded to mTOR inhibition. This case highlights the utility of targeted DNA sequencing in the management of ovarian carcinoma and demonstrates the value of tumor-agnostic targeted therapies.